PECULIARITIES OF THE SPATIAL ORGANIZATION OF THE ARTIBLE REPLACEMENT OF THE KNEE JOINT OF THE RAT DURING THE INTRODUCTION OF CRYOPRESSED PLACENT - Pelipenko, A.V.; Shepitko, V.I.; Pelipenko, L.B. (World of Medicine and Biology, 2018)
A morphological study was carried out on the quantitative and qualitative ratios of the cartilage component elements of the knee joints of rats in normal conditions and after the cryopreserved placenta administration. The articular cartilage tissues take an active part in the development and course of the most common musculoskeletal system disease - osteoarthritis, which is manifested in the vast majority of people around the world. The use of rats as an object for creating an experimental model of nonspecific arthritis has its own advantages in the study of morphological changes in articular tissues. This is the rate of obtaining research data due to accelerated regenerative ability of animals, and greater reliability due to the real possibility of performing more individual studies. The purpose of the study was to determine the peculiarities of the rat’s knee joint articular cartilage cellular structure with the cryopreserved placenta (CPP) introduction for further analysis of their changes in the development of pathological changes in the joint, mainly inflammatory, and after the therapeutic measures effect on the indicated changes. The articular surface with a relief contour was clearly defined in the obtained histological specimens, depending on the loading zones. The structures under study had a typical zonal organization: the superficial, intermediate and deep (basal) zones. Significant variability of the radial thickness may indicate the severity of the trophic processes of the given site and depend on the qualitative characteristics of surrounding tissues: subchondral bone, bone marrow, synovial membrane. The specified morphological picture is used to be explained by the presence of different loading zones on the articular surface. The density of chondrocytes location was larger closer to the superficial area and gradually decreased in the direction of the basal area. The intermediate zone transforms into the basal one without a clear boundary. Chondrocytes in this zone - hypertrophied cells - differed greatly (16.32 ± 2.231 μm) and were considered as potential major secretory and synthetic producers. Unlike cartilage of other localization, articular cartilage has two sources of nutrition: synovial fluid and blood, brought by the capillaries of the subchondral bone. The wide front of the direct contact of the cartilage with the articular cavity indicates that the supply of substances from the synovial fluid and the removal of metabolic products into the joint cavity is highly active. Consequently, the pathological process of any etiology localized in the intra-articular medium can quickly spread to adjacent tissues. The performed study showed that the cartilage tissue of rats in the area of the knee joint has a complex spatial and qualitative structure, which with the introduction of CPP reveals a wide spectrum of tissue activity in metabolic processes. The obtained characteristics of the zonal structure and features of tissue relationships can be used in further experimental studies of the comparison group.